Whom did Kiai Bisri Musthafa Address, Santri or Congregation? Language Registers in al-Ibrīz and Problems of Audience - Luthfillah, Muhammad (DINIKA : Academic Journal of Islamic Studies, 2022)
This paper offers a new reading of register polarization in two types of translations (narrative and gandul/interlinear) and the tafsīr part of al-Ibrīz li-Ma’rifat Tafsīr al-Qur’ān al-‘Azīz by Kiai Bisri Musthafa. A close reading of the narrative translation and the tafsīr requires the identification of every word comprising the speech to identify the speech register. In order to recognize the register of thegandul/interlinear translation, one must put into one’s perspective the tripartite components and properly put them into consideration. Bearing this in mind, I found that Kiai Bisri uses the register of ngoko lugu to address the audience in both parts of the narrative translation and tafsīr. In the gandul translation, one can barely identify the moment in which Kiai Bisri addresses the audience. However, I found that the very register of ngoko lugu is not exclusively exhausting the spaces. In many places the register of krama and krama inggil heavily flavor the dough. This polarization implies that the author-audience relationship is more likely that of the kiai-santri in the Islamic science class (pedagogical) instead of the kiai-congregation in the pengajian (public religious teaching, thus da’wa).